Energy analysis methodology for assessing environmental impacts. (Research results digest (National Cooperative Highway Research Program), 1979)
"An NCHRP staff digest of the essential findings from the final report on NCHRP Project 20-11B, "Toward Environmental Benefit/Cost Analysis: Energy-flow Analysis (Manual)," by M. J. Lavine, T. J. Butler, and A. H. Meyburg, Center for Environmental Research, Cornell University , Ithaca, NY."